Promoting growth and production of sunchoke (Helianthus tuberosus) by co-inoculation with phosphate solubilizing bacteria and arbuscular mycorrhizal fungi under drought - Nacoon, Sabaiporn; Seemakram, Wasan; Ekprasert, Jindarat; Jogloy, Sanun; Kuyper, Thomas W.; Mongkolthanaruk, Wiyada; Riddech, Nuntavun; Somdee, Theerasak; Boonlue, Sophon (Frontiers in Plant Science, 2022)
Due to different functions of phosphate solubilizing bacteria (PSB) and arbuscular mycorrhizal fungi (AMF), their potential synergistic effects on enhancing plant growth and yield are worth investigating, especially under adverse conditions. This work focused on the isolation of PSB and characterization for their plant growth promoting properties under drought. The most efficient P solubilizing bacterium was isolated and identified as Burkholderia vietnamiensis strain KKUT8-1. Then, a factorial experiment on the performance of sunchoke (Helianthus tuberosus) was set up with four factors, viz., PSB (presence or absence of KKUT8-1), AMF (presence or absence of Rhizophagus aggregatus), rock phosphate (RP; added or not) and moisture (well-watered (WW) or drought (DS) conditions). Sunchoke performance was enhanced by the presence of AMF, whereas addition of PSB had a positive effect on SPAD values and inulin concentration. Drought reduced plant performance, while addition of RP reduced photosynthetic rate. There was little evidence for synergistic effects between PSB and AMF, except for SPAD values and inulin concentration. Plants that were co-inoculated with AMF and PSB had highest SPAD value, shoot diameter, leaf area, leaf number, chlorophyll concentration, plant biomass, tuber production, root growth and total soluble sugar concentration. Co-inoculated plants also had increased plant water status, reduced electrolyte leakage, and reduced malondialdehyde and proline concentration. Strain KKUT8-1 is the first strain of B. vietnamiensis capable of promoting growth and yield of sunchoke. Enhanced production of sunchoke by a combination of AMF and PSB was much better than the application of RP. Our finding offers an opportunity to develop combinations of biological inoculants for increasing the growth and production of sunchoke under drought in the future.